The Influence of Job Rotation, Competency, and Audit Tenure on The Quality of Audit Results Through the Independence of the Auditors of PT Difaya Terampil Mandiri - Cahya Purnama, Deby; Razak, Ismail; S Samosir, Partogi (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to analyze the influence of work rotation, competency, and audit tenure on the quality of audit results through auditor independence. The quality of the results is an important result for stakeholders and companies that have carried out inspections. This research method involves quantitative analysis to understand the basic concept of audit result quality. Furthermore, this research will conduct a case study analysis of work rotation, competency, audit tenure, auditor independence, and the quality of audit results. The data obtained will be analyzed using path analysis. It is hoped that the research results will provide an in-depth understanding of how work rotation, competency, and audit tenure influence the quality of audit results through auditor independence. These findings can be a basis for recommending more effective implementation strategies in realizing good-quality audit results. The findings in this research are that work rotation does not have a significant effect on auditor independence and also the quality of audit results, competency, and audit tenure have a significant effect on auditor independence and the quality of audit results, auditor independence as a mediating variable can only mediate audit tenure on the quality of audit results.